Безпосередні та віддалені результати хірургічного лікування морбідного ожиріння за методикою лапароскопічного бандажування шлунка регульованою силіконовою манжетою - Черенько, С. М.; Ларін, О. С.; Товкай, О. А. (Clinical Endocrinology and Endocrine Surgery, 2013)
Results of first experience of surgical treatment of 23 morbid obese patients using methodic of laparoscopic gastric banding with the Lap-Band system (USA) were analyzed in the article. Operation demonstrated his high efficacy (95%) with zero lethality and low risk of light complications (18%). Patients with body weight index less than 50, tall stature, high level of general culture, motivation and compliance had a preferable long term results.